Mental Attitude in Complete Denture Patients: A Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Patient evaluation is the first clinical step of Complete Denture fabrication. Besides finding out intra-oralstate, the clinician also evaluates general well-being and also extra-oral state. In general well-being, thepsychological status of the patient should be evaluated. Evaluation of the mental attitude is a very importantfactor in determining the success of the complete denture. This begins immediately when the patient entersthe dental office. Patients attitude and their expectations from the treatment should be understood. If requiredcertain modifications and conditioning by the dentist should be done for better acceptance of the treatmentand a good outcome. This article is a review of the classifications proposed for evaluating the mental attitudeof the patient.